If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -23 = -5(9x + 2) Reorder the terms: -23 = -5(2 + 9x) -23 = (2 * -5 + 9x * -5) -23 = (-10 + -45x) Solving -23 = -10 + -45x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '45x' to each side of the equation. -23 + 45x = -10 + -45x + 45x Combine like terms: -45x + 45x = 0 -23 + 45x = -10 + 0 -23 + 45x = -10 Add '23' to each side of the equation. -23 + 23 + 45x = -10 + 23 Combine like terms: -23 + 23 = 0 0 + 45x = -10 + 23 45x = -10 + 23 Combine like terms: -10 + 23 = 13 45x = 13 Divide each side by '45'. x = 0.2888888889 Simplifying x = 0.2888888889
| 12+3x+3+6=5+x | | 5x+13=4+y | | 6+2r=-6-r | | x^2+18x+84=0 | | 4y-xy=2x+3 | | 4X^2-21X+5=O | | 3x+8=3-9x | | 0.20(x)=56 | | A-25=265 | | Y^2-3X=9 | | 2x^2=3364 | | 10=24-2x | | 4-5+=35 | | 1.18*16=(16-x)0.85+x*1.62 | | 7(y+2)+y=3(y+4)-8 | | 9+5n=n+5 | | 2a+3c=1 | | 0.6+0.05=3.75 | | -0.6+0.05=3.75 | | 2g+4=4g-8 | | 2(x+1)=4x-10 | | 3=h-9 | | 8-y=(7+y)3 | | 8-y=(7+y) | | x+.07x=20 | | 12-4(5a-1)=2(3a+6)-4a | | (61-10x)=(5x+7)*3 | | 61-10x=(5x+7)3 | | -3(2x+1)-20=8x+5 | | 7(3x-8)-20x=7 | | -2+8x+5=2x-21 | | 6(5x+7)=30x+42 |